Betting on death and capital markets in retirement: A shortfall risk analysis of life annuities versus phased withdrawal plans - Ivica Dus; Raimond H. Maurer; Olivia S. Mitchell (Goethe University Frankfurt, Center for Financial Studies (CFS), 2004)
How might retirees consider deploying the retirement assets accumulated in a defined contribution pension plan? One possibility would be to purchase an immediate annuity. Another approach, called the 'phased withdrawal' strategy in the literature, would have the retiree invest his funds and then withdraw some portion of the account annually. Using this second tactic, the withdrawal rate might be determined according to a fixed benefit level payable until the retiree dies or the funds run out, or it could be set using a variable formula, where the retiree withdraws funds according to a rule linked to life expectancy. Using a range of data consistent with the German experience, we evaluate several alternative designs for phased withdrawal strategies, allowing for endogenous asset allocation patterns, and also allowing the worker to make decisions both about when to retire and when to switch to an annuity. We show that one particular phased withdrawal rule is appealing since it offers relatively low expected shortfall risk, good expected payouts for the retiree during his life, and some bequest potential for the heirs. We also find that unisex mortality tables if used for annuity pricing can make women's expected shortfalls higher, expected benefits higher, and bequests lower under a phased withdrawal program. Finally, we show that delayed annuitization can be appealing since it provides higher expected benefits with lower expected shortfalls, at the cost of somewhat lower anticipated bequests.
urn:nbn:de:hebis:30-10531
Keywords: G22; G23; J26; J32; H55; 330; Insurance; Pensions; Retirement and Retirement Policies; Social Security and Public Pensions; Alterssicherung; Anlageverhalten; Private Rentenversicherung; Kapitalanlage